Geostationary Belt - State`s Territory or Province of Mankind? - Kopeć, Rafał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The geostationary orbit is a special area in outer space. Because of its distinctive characteristics, it has constantly been the subject of economic and political desirability. Space powers, taking advantage of their technological superiority and rules applied by the International Telecommunication Union (ITU) retained a privileged position. Developing countries, responding to this state of affairs, have taken a number of measures to improve their positions.
Keywords: geostationary orbit; paper satellites; orbital slots; Bogota declaration